Appraisal of Plea-Bargaining in the Criminal Justice Policy of Ethiopia - Assefa, Abebe (Bahir Dar University Journal of Law, 2022)
The administration of justice in Ethiopia has been under reform for the past fifteen years. As part of the reform, the system of plea bargaining was introduced within the first ever criminal justice policy in 2011. The policy states that the prosecutor would drop (a) count(s) of a charge or alter a charge to a lesser crime or drop certain facts of a crime and guarantee an accused a lenient sentence in return for the plea deal. Theoretical and practical controversies on plea- bargaining is still ubiquitous among researchers and practitioners.Thus, the main objective of this article is to examine and weigh the advantages and the pitfalls of the system of plea bargaining so as to bring it to the attention of the legislature. In doing so, the writer examined the theoretical aspects of plea bargaining and the contexts of criminal justice administration in Ethiopia as well as experiences of some selected countries. It is identified that plea bargaining helps reduce case backlogs and reduce costs to the state and to the defendant.It also avoids pretrial detention and severe penalties to the defendant. However, the findings also indicate that the very nature of plea bargaining, particularly the informal negotiation, would worsen the existing corruption or perceived corruption in Ethiopia so that powerful criminals may avoid punishments or may be punished with a lenient sentence which may cause for impunity. This may also deteriorate public confidence on the formal criminal justice system which could consequently hinder crime reporting. The associated trial penalty of plea bargaining also likely coerces an accused to relinquish his dueprocess rights. Therefore, the writer fears that plea bargaining would be a viable solution, at least for the time being, to the criminal justice problems of Ethiopia except may be for minor crimes.